Fundamental studies of sorghum roughages and grains. I. A study of the value of feeding the grain sorghum plant as silage and as dehydrated pellets. II. A study of the value of pelleting sorghum grain. - Richardson, D.; Smith, E.F.; Koch, B.A.; Cox, R.F.; Keltz, O.J.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
Combine-type sorghum grain is widely grown in Kansas and normally only the grain is harvested. In many instances, moisture conditions are such at harvest time that grain cannot be stored without artificially drying. Sometimes there is danger of loss to immature grain because of an early freeze. One part of this test was to study the feasibility of harvesting the entire grain sorghum plant as silage or as dehydrated pellets. Previous tests have indicated greater utilization of finely ground pelleted sorghum grain than cracked sorghum grain. The second part of the test was further work in comparing the two methods of preparation. This report is on the wintering phase of the feedlot test.
Keywords: Beef; Sorghum; Dehydrated pellets; Gain